Continuous production of biohydrogen from brewery effluent using co-culture of mutated Rhodobacter M 19 and Enterobacter aerogenes. (August 2019) - Veeramalini, J.B.; Selvakumari, I. Aberna Ebenezer; Park, Sungkwon; Jayamuthunagai, J.; Bharathiraja, B.
Graphical abstract: Highlights: Biohydrogen production using brewery effluent was investigated. Immobilized mutated Rhodobacter M 19 and Enterobacter aerogenes co-culture enhance the biohydrogen yield. The maximal biomass concentration of co-cultures strains was obtained as 3.145 g/L. The mixed culture enhances about 85% of COD removal. Gompertz model fits better with the experimental data as it contain lower RMSE values. Abstract: This study investigated the biohydrogen production from brewery effluents using free and immobilized co-culture of mutated Rhodobacter M 19 and Enterobacter aerogenes obtained from random mutagenesis with ultra violet (UV) and ethidium bromide (EtBr) treatment. The best mutant for biohydrogen production was screened based on the sugar utilization efficiency. Maximum hydrogen production of 87% was achieved with immobilized EtBr mutated co-culture. The mutant immobilized strains showed around 30% enhanced hydrogen production than wild strains at pH 6.9. Gompertz and Richard's model were used to fit the augmenting biohydrogen production and Logistics equation determines the fitness of biomass growth data. The maximal biomass concentration of co-cultures strains was 3.145 g/L with carrying capacity coefficient 0.137 h −1 . Gompertz model showed the best fit with minimal error in predicting the biohydrogen potential.